2022
DOI: 10.1186/s12890-022-02032-9
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review of effectiveness and quality assessment of patient education materials and decision aids for breathlessness

Abstract: Background Around 10% of adults suffer from clinically significant breathlessness. High quality and actionable patient education materials (PEMs) and patient decision aids (PDAs) have an important role for shared decision making and patient self-management. Objective To systematically assess the effectiveness of patient education materials (PEMs) and patient decision aids (PDAs) on clinical outcomes. Secondly, to assess the quality of PEMs and PDAs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…Community diagnostic centres where GPs can refer to Opening up direct referral to hospital-based spirometry for GPs Concerns of misdiagnosis by participants with rare conditions such as scleroderma and common ones such as asthma Providing greater access to further diagnostic tests which are not always accessible in primary care as reported in prior studies with Australian GPs and specialists 7,8 Formation of breathlessness referral services 9 to enable integrated assessment Provide primary care greater support, including digital resources and decision support systems 8 Management of chronic breathlessness Lack of nonpharmacologic support as adjuncts to treatment Previous studies have reported simple tools such as a hand-held fan to relieve breathlessness 10 Greater access to allied health and other nonphysician health professional deliver this support in addition to vital nonpharmacologic therapies such as pulmonary rehabilitation which significantly improve clinical outcomes 11 Lack of action plans and patient education materials Development of breathlessness action plans Development of high-quality patient education materials and apps for breathlessness self-management 12 hypothesised may be due to a knowledge gap regarding diagnostic tests such as spirometry. Others appreciated the GPs doing the maximum that they can and encouraged people to find a doctor that listens and understands breathlessness.…”
Section: Low Utilisation Of Spirometry To Aid Diagnosis Of Chronic Br...mentioning
confidence: 99%
“…Community diagnostic centres where GPs can refer to Opening up direct referral to hospital-based spirometry for GPs Concerns of misdiagnosis by participants with rare conditions such as scleroderma and common ones such as asthma Providing greater access to further diagnostic tests which are not always accessible in primary care as reported in prior studies with Australian GPs and specialists 7,8 Formation of breathlessness referral services 9 to enable integrated assessment Provide primary care greater support, including digital resources and decision support systems 8 Management of chronic breathlessness Lack of nonpharmacologic support as adjuncts to treatment Previous studies have reported simple tools such as a hand-held fan to relieve breathlessness 10 Greater access to allied health and other nonphysician health professional deliver this support in addition to vital nonpharmacologic therapies such as pulmonary rehabilitation which significantly improve clinical outcomes 11 Lack of action plans and patient education materials Development of breathlessness action plans Development of high-quality patient education materials and apps for breathlessness self-management 12 hypothesised may be due to a knowledge gap regarding diagnostic tests such as spirometry. Others appreciated the GPs doing the maximum that they can and encouraged people to find a doctor that listens and understands breathlessness.…”
Section: Low Utilisation Of Spirometry To Aid Diagnosis Of Chronic Br...mentioning
confidence: 99%
“…During 2022, two comprehensive reviews of educational resources focussing upon breathlessness as a symptom were published concerning publicly available patient education materials (PEMs) 37▪▪ and the self-management mobile Apps 38▪▪ . The 88 PEMs reviewed included paper-based/printable PDFs ( n =52, 59%) and static webpages ( n =35, 40%).…”
Section: Patient Education Resources For Breathlessnessmentioning
confidence: 99%
“…This equates to the USA educational grade for students aged ≥17 years, which is often considered to reflect skilled readers. Less than half of the PEMs ( n =35, 40%) scored at a Grade level ≤8.0 (Supplemental Table 4 in 37▪▪ ). Using the PEMAT-Printable, 92% of PEMs scored above the recommended threshold of ≥70% for understandability 24 , with 40% scoring ≥70% for actionability (Supplemental Table 4 in 37▪▪ ).…”
Section: Patient Education Resources For Breathlessnessmentioning
confidence: 99%
See 1 more Smart Citation
“…There is a paucity of evidence to suggest patient educational materials (including PtDAs) are beneficial for reducing breathlessness and improving psychological well-being across acute respiratory diseases. 27 Two systematic reviews have been published to synthesise evidence on the impact of SDM interventions on people with asthma 28 and cystic fibrosis 29 but they found the evidence base to be very limited and too heterogeneous to draw meaningful conclusions about the relationship between the interventions and improved SDM or downstream health-related outcomes and nearly all the review population were children and adolescents. Therefore, there is a clear need to evaluate the efficacy of SDM interventions on adult patients living with CRD (eg, COPD, asthma, idiopathic pulmonary fibrosis, lung cancer).…”
Section: Introductionmentioning
confidence: 99%